Multiple Dimensions and Correlates of Fatigue in Individuals on Hemodialysis. - Joshwa, Bincy; Peters, Rosalind M.; Malek, Moh H.; Yarandi, Hossein N.; Campbell, Margaret L. (Nephrology Nursing Journal, 2020)
This study examined the severity, pattern, and correlates of fatigue among adults undergoing hemodialysis. Measures included the Piper Fatigue Scale (PFS-12), Patient-Reported Outcomes Measurement Information System (PROMIS) -- Fatigue, Charlson Comorbidity Index, and Six-Minute Walk Test (6MWT). Patients were excluded if mobility or cardiovascular issues prevented conducting the 6MWT. Participants were 86 cognitively intact adults (M = 61.7 years, SD = 13.81), predominantly male (58.1%), and African American (48.8%), with 80% reporting fatigue in the week prior to hemodialysis. Significant increases were noted in sensory and cognitive fatigue from pre- to post-dialysis, while the 6MWT distance decreased significantly pre- to post-dialysis. Factors significantly associated with pre-dialysis fatigue included low hemoglobin, younger age, and living with someone else, while comorbidities and dialysis inadequacy were trending to significant associations with fatigue.